A Debugger Interface for Parallel Programs - Stringhini, Denise; Navaux, Philippe O. A.; Kergommeaux, Jacques Chassin de (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
This paper describes the debugger interface that has been developed to provide a complete debugging tool for parallel application programmers. PADI (Parallel Debugger Interface) is a symbolic on-line debugging interface whose main goal is to provide easy interaction and intuitive interface for programmers. To achieve these goals, PADI implements visualization support and selection mechanism. The visualization support helps users following the changes of process states during the debugging session as well as it gives access to all processes that are running under the control of the debugging environment. The selection mechanism helps users choosing the processes they want to control and visualize.